Analisis Perbandingan Kinerja Finacial pada PT. Bumi Serpong Damai Tbk dengan PT. Summarecon Agung Tbk yang Terdaftar di Bursa Efek Indonesia - Matias Yoq; Sri Hermuningsih (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine the comparison of financial performance of PT. Bumi Serpong Damai Tbk with PT. Summarecon Agung Tbk is seen from the ratio of liquidity, solvency and activity. Data collection techniques with literature and documentation. Data analysis used in liquidity ratio analysis consists of Current Ratio (CR), and Quick Ratio (QR), solvency ratios namely Total Debt to Equity Ratio and Total Debt to Total Asset Ratio. Then the Activity Ratio is the receivables turnover ratio and inventory turnover ratio. The results showed that the overall financial performance of PT Bumi Serpong Damai Tbk and PT. Summarecon Agung Tbk is arguably good. PT. Summarecon Agung Tbk has a slightly lower level of debt risk when compared to PT. Bumi Serpong Damai Tbk. PT. Bumi Serpong Damai Tbk is more effective in conducting profitability ratio compared to PT. Summarecon Agung Tbk. PT. Summarecon Agung Tbk is able to sell and replace inventory quickly compared to PT. Bumi Serpong Damai Tbk.